2009
DOI: 10.1111/j.1468-2982.2008.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine is a Risk Factor for Hypertensive Disorders in Pregnancy: A Prospective Cohort Study

Abstract: The aim was to assess whether women suffering from migraine are at higher risk of developing hypertensive disorders in pregnancy. In a prospective cohort study, performed at antenatal clinics in three maternity units in Northern Italy, 702 normotensive women with singleton pregnancy at 11-16 weeks' gestation were enrolled. Women with a history of hypertensive disorders in pregnancy or presenting chronic hypertension were excluded. The presence of migraine was investigated according to International Headache So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 38 publications
12
92
4
2
Order By: Relevance
“…287 Interestingly, there is an emerging literature on the association between migraines and preeclampsia. [288][289][290] The most recent analysis of the United Kingdom Obstetric Surveillance System found 30 cases of antenatal stroke, for an estimated incidence of 1.5 cases per 100 000 women who delivered babies (95% CI, 1.0-2.1). Factors associated with increased risk of antenatal stroke were history of migraine (adjusted OR, 8.5; 95% CI, 1.5-62.1), gestational diabetes (adjusted OR, 26.8; 95% CI, 3.2-∞), and preeclampsia or eclampsia (adjusted OR, 7.7; 95% CI, 1.3-55.7).…”
Section: Strokementioning
confidence: 99%
“…287 Interestingly, there is an emerging literature on the association between migraines and preeclampsia. [288][289][290] The most recent analysis of the United Kingdom Obstetric Surveillance System found 30 cases of antenatal stroke, for an estimated incidence of 1.5 cases per 100 000 women who delivered babies (95% CI, 1.0-2.1). Factors associated with increased risk of antenatal stroke were history of migraine (adjusted OR, 8.5; 95% CI, 1.5-62.1), gestational diabetes (adjusted OR, 26.8; 95% CI, 3.2-∞), and preeclampsia or eclampsia (adjusted OR, 7.7; 95% CI, 1.3-55.7).…”
Section: Strokementioning
confidence: 99%
“…However, some of these cases may have been caused by secondary headaches, in particular those linked to hypertensive disorders [5,8]. In fact, our data did not allow us to investigate this aspect.…”
Section: Discussionmentioning
confidence: 72%
“…In a prospective cohort study from three clinical units, designed to examine the association of migraine with hypertensive disorders of pregnancy, Faccinetti et al 9 reported as secondary outcomes that birth before 37 weeks and birth weight below 2500 g were non-significantly more frequent in the infants born to 270 women with migraine as compared with 432 women without migraine. The ORs (1.64 (0.85 to 3.16) and 1.97 (0.98, 3.98)) were further lowered by adjustment for age, family history of hypertension and smoking.…”
Section: Migraine and Preterm Birthmentioning
confidence: 99%
“…6 There is a striking increase in frequency of pregnancy-associated stroke in women with a history of migraine, although the absolute level of that risk is low. 7 Migraine is associated with pre-eclampsia, [8][9][10][11] itself a marker of risk for later ischemic stroke 12 Other disorders influenced by migraine history include endometriosis and metrorrhagia. 13 Despite these observations linking endocrine and reproductive function as well as vascular disorders with migraine, and the high prevalence of migraine in women of reproductive age, there has been relatively little attention given to whether maternal migraine or its treatment influence pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%